Prokineticin 1–prokineticin receptor 1 signaling in trophoblast promotes embryo implantation and placenta development - Ewelina Goryszewska-Szczurek (Nature Portfolio, 2021)
Abstract Successful pregnancy establishment in mammals depends on proper embryo-maternal communication. Prokineticin 1 (PROK1) is a secretory protein that exerts pleiotropic functions in various tissues. Despite the studies that have primarily been performed with human cell lines and mice, the function of PROK1 in trophoblasts has still not been fully elucidated. Hence, the aim of this study was to establish the role of PROK1 in trophoblasts during implantation and placentation. Prokineticin 1 mRNA was elevated in porcine trophoblasts during implantation and the early placentation period. Furthermore, we reveal that PROK1–PROKR1 signaling induces the expression of genes involved in the regulation of angiogenesis, immunological response, trophoblast cell adhesion, invasion, and proliferation, as well as stimulating phosphorylation of MAPK and PTK2. Ingenuity Pathway Analysis identified the aforementioned and also other functions associated with PROK1-regulated genes/proteins, such as cell-to-cell contact, epithelial tissue differentiation, Ca2+ release, lipid synthesis, and chemotaxis. We also showed evidence that PROK1 acting via PROKR1 increased trophoblast cell proliferation and adhesion. The PROK1-stimulated cell proliferation was mediated by PI3K/AKT/mTOR, MAPK, and cAMP, whereas adhesion was mediated by MAPK and/or PI3K/AKT signaling pathways. Concluding, our study suggests that PROK1 plays a pleiotropic role in trophoblast function during implantation and early placentation.